Analisa pengaruh pemahaman prinsip good corporate governance, pengendalian intern, komitmen organisasi terhadap kinerja pemerintah desa Kateguhan, Sawit, Boyolali - Frisca Yustin; Wikan Budi Utami; Sri Laksmi Pardanawati (ITB AAS INDONESIA, 2022)
This study was used to determine the effect of understanding the principles of Good Corporate Governance, internal control, organizational commitment on the performance of the government of Kateguhan Village, Palm Oil, Boyolali using quantitative data analysis with the help of the SPSS 16.0 statistical program, with the conclusion that understanding the principles of Good Corporate Governance has a t count of 2,030 > t table 1.989 with a significance of 0.045 less than (a) 5% (0.05), which means understanding the principles of Good Corporate Governance has a significant positive effect on performance, the internal control variable has a t count of 2.332 t table 1.989 with a significance of 0.022 less than (a ) 5% (0.05), which means that internal control has a positive and significant effect on organizational performance and commitment has a t count of 2.452 t table 1.989 with a significance of 0.016 less than (a) 5% (0.05), which means commitment organization has a positive and significant impact on government performance